ANALISIS WARM WATER LAYER SEBAGAI SISTEM PROTEKSI PADA REAKTOR SERBA GUNA G. A. SIWABESSY DENGAN MENGGUNAKAN KOMPUTASI DINAMIKA FLUIDA - , TIAR FRIDIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Warm water layer system is a protection system that protect the environment and the workers above of the reactor pool from radiation exposure which carried by the primary coolant. The system forms the warm water layer at the surface of reactor pool for about 1,5 m thick and temperature for about 8 to 10 oC slightly above of the reactor pool temperature. Computational fluid dynamics can be used to analyze the characteristics of the warm water layer. One of the powerful computational fluid dynamics software is FLUENT and it is used to anlayze the warm water layer at the G.A. Siwabessy multipurpose reactor. The results show that the increasing of warm water inlet temperature can increase the warm water layer temperature range which the safety system required. But it does not effect to the warm water layer thickness and population. In the other hand, the increasing of warm water layer inlet flow can increase the warm water layer thickness but not to the warm water layer temperature range. The effectiveness of warm water layer initially starts at 15 m3/h and 50 oC of the warm water inlet flow and temperature. At this condition, the warm water layer can block the primary coolant to reach the reactor poolâs surface.